2019
DOI: 10.1002/mbo3.815
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal regulatory domain of the ε subunit of FoF1 ATP synthase enhances the ATP‐dependent H+ pumping that is involved in the maintenance of cellular membrane potential in Bacillus subtilis

Abstract: The ε subunit of FoF1‐ATPase/synthase (FoF1) plays a crucial role in regulating FoF1 activity. To understand the physiological significance of the ε subunit‐mediated regulation of FoF1 in Bacillus subtilis, we constructed and characterized a mutant harboring a deletion in the C‐terminal regulatory domain of the ε subunit (ε∆C). Analyses using inverted membrane vesicles revealed that the ε∆C mutation decreased ATPase activity and the ATP‐dependent H+‐pumping activity of FoF1. To enhance the effects of ε∆C mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…This seems to take place because the Bs-ε is somehow relieving the intrinsic kinetic MgADP inhibition [53]. This Bs-ε activating effect has also been demonstrated in the full BsF1FO-ATPase [54]. Furthermore, it has also been shown that the last five residues of the very C-terminus of the ε subunit of the F-ATP synthase from E. coli (Ec-ε) enhance the clockwise F-ATP synthase turnover and the respiratory E. coli growth.…”
Section: Inhibitory and Non-inhibitory ε Subunits Of The Bacterial F ...mentioning
confidence: 83%
“…This seems to take place because the Bs-ε is somehow relieving the intrinsic kinetic MgADP inhibition [53]. This Bs-ε activating effect has also been demonstrated in the full BsF1FO-ATPase [54]. Furthermore, it has also been shown that the last five residues of the very C-terminus of the ε subunit of the F-ATP synthase from E. coli (Ec-ε) enhance the clockwise F-ATP synthase turnover and the respiratory E. coli growth.…”
Section: Inhibitory and Non-inhibitory ε Subunits Of The Bacterial F ...mentioning
confidence: 83%
“… 9 , 21 This is the mechanism targeted by PPI therapy. 7 , 8 , 16 H + /K + ATPases contain the catalytic α-subunit and non-catalytic glycosylation β-subunit. The α-subunit of the H + /K + ATPases of different species is made up of 1035 amino acids and includes the catalytic center, which resides in the large cytoplasmic domain of the enzyme.…”
Section: Gastric Proton Pump H + /K + mentioning
confidence: 99%
“…9 As a byproduct of the pump activity, a pH gradient forms on either side of the membrane. Four types of proton pumps with ATPase activity have been recognized: P-type, [10][11][12][13][14] F-type, [15][16][17] V-type, [18][19][20] and ABC ATPases. 18…”
Section: Introductionmentioning
confidence: 99%
“…The ATP-driven H + pump activity of CF o CF 1 in the thylakoid membranes was measured according to the fluorescence quenching of ACMA based on a previous method with some modifications ( 36 , 55 ). The emitted fluorescence of ACMA (excitation at 410 nm, emission at 480 nm) was measured using a FP-8500 spectrofluorometer (Jasco), in which the temperature in the sample chamber was 25 °C.…”
Section: Methodsmentioning
confidence: 99%